Hubungan Paritas dan Inisiasi Menyusu Dini (IMD) dengan Involusi Uteri pada Ibu Nifas - Khoirunnisa, Fania Nurul; Nasriyah; Hidayah, Roudhotun Mahfiroh Arinal (ProHealth Journal, 2025)
Uterine involution is an important process indicating maternal recovery during the postpartum period. The speed of uterine involution is influenced by various factors, including the mother's age, number of previous births (parity), exclusive breastfeeding, implementation of early initiation of breastfeeding (IMD), and early mobilization after giving birth. Breastfeeding has a crucial role in accelerating uterine involution, because through this process, the baby's sucking on the mother's nipple stimulates uterine contractions. IMD, namely the baby's first breastfeeding immediately after birth, is one important step in supporting this process. Apart from that, parity or the number of previous births also influences the uterine involution process. In mothers giving birth for the first time, the involution process can take place a little differently compared to mothers who have given birth before. This study aims to analyze the relationship between parity and early initiation of breastfeeding (IMD) with uterine involution in postpartum mothers at the PKU Muhammadiyah Mayong Jepara Hospital. Researchers used a quantitative type of research with a cross sectional design. This research used a sample of 36 respondents calculated using the Slovin formula. The instruments used in this research were questionnaires and observation sheets. Data were analyzed using the chi-square test. The results showed that the average patient age was 27 years, most respondents had completed high school education with a frequency of 27 people (75%). The correlation test concluded that there was no relationship between parity (p value = 0.582) with uterine involution in postpartum mothers and there was a relationship between IMD (p = 0.011) with uterine involution in postpartum women at the PKU Muhammadiyah Mayong Jepara Hospital.